PERLINDUNGAN HUKUM BAGI WARGA NEGARA DALAM PELAKSANAAN MUTASI PEGAWAI NEGERI SIPIL - Muhammad Yassin (Yuridika, 2016)
Civil servant is the incumbent Government in doing a service to the community. To meet the needs of employees in the Agency-agencies or areas that need or are experiencing a shortage of substitute employees Transfer of civil servants or mutations. The occurrence of a mutation or the transfer of work areas occurs only on civil servants, not government employees with the agreement because the civil servant has no agreement or contract work but hired a public agreement was generally recognized by many countries. In practice, Transfer of civil servants is one of the activities closely associated with the emergence of imbalance between the rights and obligations of civil servants as the civilian apparatus of state and as the citizens. Therefore, it is necessary to have legal protection for civil servants in the implementation of the transfer of civil servants. In relation to the implementation of the mutation, any civil servant who is transferred must be treated equally, whether it is the right or obligation of the civil servant concerned. Mutations are not the cause of the reduced rights, such as salary, leave, opportunities for promotion, even safe and healthy working conditions. Implementation of the mutation should also ensure that the workload and related employee responsibilities will remain the same as those performed in the previous workplace.